STABILIZATION OF HISTORICAL ARCHIVES IN MEKELLE CITY RESCUE OF FIRE AND WATER DAMAGED DOCUMENTS, Report - Asfha, Alula Tesfay; Dawit Gebrehiwot; Selam Gebrekristos; Yirga Asefa; Nega Tadesse (Mekelle University, 2024)
INTRODUCTION: The archival materials within the Mekelle Municipality building face severe threats due to poor storage conditions and safety hazards. An exposed electrical panel with open wires presents a significant fire risk, which became a reality in a recent incident likely triggered by compromised wiring or nearby cooking activities. This fire caused substantial damage to numerous documents, necessitating the urgent intervention of the municipal fire brigade. Although their quick response prevented further loss, the water used to extinguish the flames soaked many records, hastening their deterioration. The wet papers quickly morphed into a pulpy, unidentifiable mass, combining soot, dirt, and charred remnants, rendering many documents permanently unreadable. This situation underscores the urgent need for immediate archival preservation efforts, as each document represents a vital piece of Mekelle's history that must be rescued before it is lost forever.
Keywords: Archive; Mekelle; Postconflict